2020
DOI: 10.3390/ijms21217966
|View full text |Cite
|
Sign up to set email alerts
|

Differential Defense Responses of Upland and Lowland Switchgrass Cultivars to a Cereal Aphid Pest

Abstract: Yellow sugarcane aphid (YSA) (Sipha flava, Forbes) is a damaging pest on many grasses. Switchgrass (Panicum virgatum L.), a perennial C4 grass, has been selected as a bioenergy feedstock because of its perceived resilience to abiotic and biotic stresses. Aphid infestation on switchgrass has the potential to reduce the yields and biomass quantity. Here, the global defense response of switchgrass cultivars Summer and Kanlow to YSA feeding was analyzed by RNA-seq and metabolite analysis at 5, 10, and 15 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Proteomic studies using switchgrass are relatively limited [19][20][21][22][23] but can bolster more extensive evaluation of the physiological and genetic responses of this crop to pathogens that impact yield and quality. The proteomic data in this study broadly support earlier observations [6,13,[24][25][26][27][28][29][30] on the responses of Summer plants to biotic stressors while providing greater depth to the changes in cellular metabolism occurring in switchgrass in response to prolonged stress caused by Pn.…”
Section: Discussionsupporting
confidence: 87%
“…Proteomic studies using switchgrass are relatively limited [19][20][21][22][23] but can bolster more extensive evaluation of the physiological and genetic responses of this crop to pathogens that impact yield and quality. The proteomic data in this study broadly support earlier observations [6,13,[24][25][26][27][28][29][30] on the responses of Summer plants to biotic stressors while providing greater depth to the changes in cellular metabolism occurring in switchgrass in response to prolonged stress caused by Pn.…”
Section: Discussionsupporting
confidence: 87%
“…PviAPX expression is induced during leaf senescence [ 57 ], and biotic stress [ 28 , 58 ]. Since biotic stress in switchgrass also activates other genes associated with phenylpropanoid metabolism and increases levels of defensive compounds synthesized from caffeic acid [ 28 , 58 , 59 ], it is plausible that PviAPX is involved in these processes along with its expected role in ROS homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches are powerful tools in the identification of genome-wide regulatory patterns in plants under biotic and abiotic stress conditions. In switchgrass, co-expression analysis has been used to establish the potential transcriptional regulatory networks in heat, drought, and biotic stress conditions (Hayford et al, 2022; Pingault et al, 2020). Recently, a comprehensive, transcriptomic study on several panicoid grasses, including switchgrass, revealed that machine learning approaches can be implemented to predict cold stress responses of genes within and between species based on nucleotide frequencies in promoter regions of genes, among other features (Meng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%